Refinement of Metrics: Erdős Number, a Case Study - Lock, Kayla; Pong, Wai Yan; Wittmond, Alexander (The PUMP Journal of Undergraduate Research, 2019)
We introduce a concept called refinement and provide two different ways of refining metrics. By applying these methods we produce several refinements of the shortest-path distance on the collaboration graph and hence a couple of new versions of the Erdős number.